COVID‐19‐convalescence phase unmasks a silent myocardial infarction due to coronary plaque rupture. (6th January 2021) - Tschöpe, Carsten; Sherif, Mohammad; Anker, Markus S.; Geisel, Dominik; Kuehne, Titus; Kelle, Sebastian
Abstract: Increased risk of cardiovascular complications during and post‐COVID‐19 infection is more and more recognized—including myocarditis, arrhythmias, and myocardial infarctions (MIs). The mechanisms leading to these complications are direct virus‐induced injuries, as well as potential thrombotic and inflammatory‐induced mechanisms. To the latter, inflammatory plaque instability and plaque rupture are discussed entities contributing to MI‐induced post‐COVID‐19 complications. Our case report describes the first time, when a temporary impairment of LVEF in the COVID‐19‐convalescence phase unmasks a silent MI due to coronary plaque rupture by using invasive (OCT) and non‐invasive (CMR) modalities. Myocardial infarction might be an important differential diagnosis to consider in deteriorating patients with COVID‐19, especially if dyspnoea persists after acute infection.